Design Procedures of Reinforced Concrete Framed Buildings in Nepal and its Impact on Seismic Safety. Issue 10 (November 2014) - Chaulagain, Hemchandra; Rodrigues, Hugo; Spacone, Enrico; Varum, Humberto
The present paper analyses the design procedure and its impact on seismic safety of the structures. For this, a representative reinforced concrete frame building (WDS) is designed and the results are compared with similar buildings detailed with: i ) Current Construction Practices (CCP); ii ) the Nepal Building Code (NBC) and iii) the Modified Nepal Building Code (NBC+) recommendations. The seismic performance evaluation is done with global strength, inter-storey drift and displacement of the structures. Likewise, the sensitivity of the structural and geometrical parameters of the RC frame building is studied through nonlinear analysis. The study parameters considered for parametric analysis are column size, beam size, inter-storey height, bay length, bay width, and compressive strength of concrete. The results show that the influence on the structural behaviour, particularly by variation in column size and inter-storey height. Additionally, the influence of the seismic zone factor on reinforcement demand of the structure is studied. The result shows that structures designed for high to medium seismic hazard demands double the reinforcement in beams compared to structures in low seismic zone.